# Generalizations of Cauchy-Schwarz inequality in unitary spaces

## Abstract

In this paper, we give a generalization of Cauchy-Schwarz inequality in unitary spaces and obtain its integral analogs. As an application, we establish an inequality for covariances.

## 1 Introduction

Let u and v be two vectors in a unitary space $$\mathbb{H}$$. The Cauchy-Schwarz inequality is well known,

$$\bigl\vert \langle u,v\rangle\bigr\vert \leq\|u\|\cdot\|v\|,$$
(1.1)

where $$\langle\cdot,\cdot\rangle$$ and $$\|\cdot\|$$ denote the inner product and norm in $$\mathbb{H}$$, respectively. Its integral form in the space of real-valued functions $$L^{2}[a,b]$$ is

$$\biggl(\int_{a}^{b}f\cdot g \, d\mu \biggr)^{2}\leq \biggl(\int_{a}^{b}f^{2} \, d\mu \biggr) \biggl(\int_{a}^{b}g^{2} \, d\mu \biggr).$$
(1.2)

The Cauchy-Schwarz inequality is one of the most important inequalities in mathematics. To date, a large number of generalizations and refinements of the inequalities (1.1) and (1.2) have been investigated in the literature (see [1] and references therein, also see [2â€“9]).

In this note, we will present some new generalizations of the Cauchy-Schwarz inequality (1.1).

Suppose that $$\mathbb{H}$$ is a unitary space (complex inner product space) with standard inner product $$\langle\cdot,\cdot\rangle$$ and norm $$\|\cdot\|$$, namely $$\langle x,y\rangle=x^{T}\overline{y}$$ and $$\|x\| =\sqrt{\langle x,x\rangle}$$ (see [10]). Let $$X=( x_{1},x_{2},\ldots,x_{n})$$ denote the n-tuple of vectors $$x_{i} \in \mathbb{H}$$, $$i=1,\ldots,n$$. For two n-tuples $$X=(x_{1},\ldots,x_{n})$$ and $$Y=(y_{1},\ldots,y_{n})$$ of $$\mathbb{H}$$, we define this A-product of vector $$x_{i}$$ and $$y_{i}$$ for X and Y by

$$x_{i}\otimes_{A} y_{i}=\langle x_{i},y_{i}\rangle-\langle x_{i},b\rangle- \langle a,y_{i}\rangle,$$

where $$a=\frac{x_{1}+\cdots+x_{n}}{n}$$ and $$b=\frac{y_{1}+\cdots+y_{n}}{n}$$.

Our main results are the following theorems.

### Theorem 1

Let $$X=( x_{1},\ldots,x_{n})$$ and $$Y=(y_{1},\ldots ,y_{n})$$ be two n-tuples of the unitary space $$\mathbb{H}$$, then

$$\sum_{i=1}^{n}| x_{i} \otimes_{A}y_{i}|\leq \Biggl(\sum ^{n}_{i=1}\|x_{i}\|^{2} \Biggr)^{1/2} \Biggl(\sum^{n}_{i=1} \|y_{i}\|^{2} \Biggr)^{1/2}.$$
(1.3)

Equality holds if $$y_{i}=(x_{i}-2a)\lambda$$ ($$i=1,\ldots,n$$) for any $$\{ x_{1},\ldots, x_{n}\}$$, where Î» is a non-negative constant.

In particular, if $$n=1$$, then (1.3) is the Cauchy-Schwarz inequality (1.1).

For complex numbers $$\mathbb{C}$$, by TheoremÂ 1, we have the following.

### Corollary 1

Suppose that $$x_{1},\ldots,x_{n}$$ and $$y_{1},\ldots ,y_{n}$$ are complex numbers. Set

$$a=\frac{x_{1}+\cdots+x_{n}}{n}, \qquad b=\frac{y_{1}+\cdots+y_{n}}{n},$$

then

$$\Biggl(\sum_{i=1}^{n}|x_{i}y_{i}-a y_{i} -b x_{i} | \Biggr)^{2}\leq \Biggl(\sum _{i=1}^{n}|x_{i}|^{2} \Biggr) \Biggl(\sum_{i=}^{n}|y_{i}|^{2} \Biggr) .$$

Equality holds if $$y_{i}=(x_{i}-2a)\lambda$$ ($$i=1,\ldots,n$$) for any $$\{x_{1},\ldots, x_{n}\}$$, where Î» is a non-negative constant.

Let $$H\oplus H\oplus\cdots\oplus H$$ denote the direct sum of n unitary space $$\mathbb{H}$$ with norm $$\|X\|= (\sum_{i=1}^{n}\|x_{i}\|^{2} )^{\frac{1}{2}}$$. Set $$f(X,Y)=\sum_{i=1}^{n} x_{i}\otimes_{A}y_{i}$$. Since $$f(X,X)$$ is not always non-negative, $$f(X,Y)$$ is not an inner product in the above direct sum. Hence, (1.3) is different from the Cauchy-Schwarz inequality in the above direct sum.

If we set $$|X\otimes_{A} Y|=\sum_{i=1}^{n}| x_{i}\otimes_{A}y_{i}|$$, then (1.3) can be restated as

$$|X\otimes_{A} Y|\leq\|X\|\cdot\|Y\|.$$

Furthermore, we obtain the following integral form of (1.3) (only consider real-valued functions).

### Theorem 2

Let Î¼ be a positive measure such that $$\mu(\Omega)=1$$, f and g be real-valued functions in $$L^{2}(\mu)$$, and let

$$f\otimes_{A}g(x)=f(x)\cdot g(x)-f(x)\cdot\int_{\Omega}g\, d\mu-g(x)\cdot\int_{\Omega}f\, d\mu,$$

then

$$\biggl(\int_{\Omega}|f\otimes_{A}g|\, d\mu \biggr)^{2}\leq \biggl(\int_{\Omega}f^{2}\, d \mu \biggr) \biggl(\int_{\Omega}g^{2}\, d\mu \biggr).$$
(1.4)

Equality holds if $$g(x)=(f(x)-2 \int_{\Omega}f \, d\mu)\lambda$$, where Î» is a non-negative constant.

## 2 The proofs of the theorems

### Proof of TheoremÂ 1

Using the basic properties of the norm of a unitary space, we get

\begin{aligned} \sum_{i=1}^{n}\|y_{i}-2b \|^{2}&=\sum_{i=1}^{n} \langle y_{i}-2b,{y_{i}}-2{b}\rangle \\ &=\sum_{i=1}^{n} \bigl(4\|b \|^{2}-2\langle y_{i},{b}\rangle-2\langle b,{y_{i}}\rangle+\|y_{i}\|^{2} \bigr) \\ &=4n\|b\|^{2}-2\Biggl\langle \sum_{i=1}^{n}y_{i},{b} \Biggr\rangle -2\Biggl\langle b,{\sum_{i=1}^{n}y_{i}} \Biggr\rangle +\sum_{i=1}^{n} \|y_{i}\|^{2} \\ &=4n\|b\|^{2}-2n\|b\|^{2}-2n\|b\|^{2}+\sum _{i=1}^{n}\|y_{i}\|^{2} \\ &=\sum_{i=1}^{n}\|y_{i} \|^{2}. \end{aligned}
(2.1)

By (2.1), using the Cauchy-Schwarz inequality (1.1) and the discrete form of the Cauchy-Schwarz inequality, it follows that

\begin{aligned} \sum_{i=1}^{n}\bigl\vert \langle x_{i},y_{i}-2b\rangle\bigr\vert &\leq\sum _{i=1}^{n}\|x_{i}\|\cdot\| y_{i}-2b\| \\ &\leq \Biggl(\sum_{i=1}^{n} \|x_{i}\|^{2} \Biggr)^{\frac{1}{2}} \Biggl(\sum _{i=1}^{n}\| y_{i}-2b\|^{2} \Biggr)^{\frac{1}{2}} \\ &= \Biggl(\sum_{i=1}^{n}\|x_{i} \|^{2} \Biggr)^{\frac{1}{2}} \Biggl(\sum_{i=1}^{n} \|y_{i}\| ^{2} \Biggr)^{\frac{1}{2}}. \end{aligned}
(2.2)

Similarly to (2.2), we have

$$\sum_{i=1}^{n}\bigl\vert \langle x_{i}-2a,y_{i}\rangle\bigr\vert \leq \Biggl(\sum ^{n}_{i=1}\|x_{i}\| ^{2} \Biggr)^{\frac{1}{2}} \Biggl(\sum^{n}_{i=1} \|y_{i}\|^{2} \Biggr)^{\frac{1}{2}}.$$
(2.3)

Combining (2.2) and (2.3), we infer that

\begin{aligned} \sum_{i=1}^{n} \vert x_{i} \otimes_{A}y_{i}\vert &=\frac{1}{2}\sum _{i=1}^{n}\bigl\vert 2\langle x_{i},y_{i} \rangle-\langle x_{i},2b\rangle-\langle2a,y_{i}\rangle\bigr\vert \\ &=\frac{1}{2}\sum_{i=1}^{n}\bigl\vert \langle x_{i},y_{i}-2b\rangle+\langle x_{i}-2a,y_{i}\rangle\bigr\vert \\ &\leq\frac{1}{2}\sum_{i=1}^{n}\bigl\vert \langle x_{i},y_{i}-2b\rangle\bigr\vert + \frac{1}{2}\sum_{i=1}^{n}\bigl\vert \langle x_{i}-2a,y_{i}\rangle\bigr\vert \\ &\leq \Biggl(\sum_{i=1}^{n} \|x_{i}\|^{2} \Biggr)^{\frac{1}{2}} \Biggl(\sum _{i=1}^{n}\| y_{i}\|^{2} \Biggr)^{\frac{1}{2}}. \end{aligned}

This is the inequality (1.3), as desired.â€ƒâ–¡

### Proof of TheoremÂ 2

We first prove the following inequality:

$$\int_{\Omega}\biggl\vert f \biggl(g-2\int_{\Omega}g\, d\mu \biggr)\biggr\vert \, d\mu\leq \biggl(\int_{\Omega}f^{2} \, d\mu \biggr)^{\frac{1}{2}} \biggl(\int_{\Omega}g^{2}\, d\mu \biggr)^{\frac{1}{2}}.$$
(2.4)

In fact, by the Cauchy-Schwarz inequality (1.2), we obtain

\begin{aligned}& \int_{\Omega}\biggl\vert f \biggl(g-2\int_{\Omega}g\, d\mu \biggr)\biggr\vert \,d\mu \\& \quad \leq \biggl(\int_{\Omega}f^{2} \,d\mu \biggr)^{\frac{1}{2}} \biggl(\int_{\Omega}\biggl(g-2\int_{\Omega}g\, d\mu \biggr)^{2}\,d\mu \biggr)^{\frac{1}{2}} \\& \quad = \biggl(\int_{\Omega}f^{2} \,d\mu \biggr)^{\frac{1}{2}}\cdot \biggl(\int_{\Omega}\biggl(4 \biggl( \int_{\Omega}g \,d\mu \biggr)^{2}-4 \biggl(\int _{\Omega}g \,d\mu \biggr)\cdot g+g^{2} \biggr)\,d\mu \biggr)^{\frac{1}{2}} \\& \quad = \biggl(\int_{\Omega}f^{2} \,d\mu \biggr)^{\frac{1}{2}}\cdot \biggl(4 \biggl(\int_{\Omega}g \,d\mu \biggr)^{2}\mu(\Omega)-4 \biggl(\int_{\Omega}g \,d\mu \biggr)^{2}+\int_{\Omega}g^{2} \,d\mu \biggr)^{\frac{1}{2}} \\& \quad = \biggl(\int_{\Omega}f^{2} \,d\mu \biggr)^{\frac{1}{2}} \biggl(\int_{\Omega}g^{2} \,d\mu \biggr)^{\frac{1}{2}}. \end{aligned}

This is the inequality (2.4).

Similarly, we have

$$\int_{\Omega}\biggl\vert g \biggl(f-2\int_{\Omega}f\, d\mu \biggr)\biggr\vert \, d\mu\leq \biggl(\int_{\Omega}f^{2}\, d\mu \biggr)^{\frac{1}{2}} \biggl(\int_{\Omega}g^{2}\, d\mu \biggr)^{\frac{1}{2}}.$$
(2.5)

From (2.4) and (2.5), we find that

\begin{aligned}& \int_{\Omega}|f\otimes_{A}g| \, d\mu \\& \quad = \frac{1}{2}\int_{\Omega}\biggl\vert \biggl(g-2\int _{\Omega}g\, d\mu \biggr)f+ \biggl(f-2\int_{\Omega}f\, d\mu \biggr)g\biggr\vert \, d\mu \\& \quad \leq\frac{1}{2} \biggl(\int_{\Omega}\biggl\vert f \biggl(g-2\int_{\Omega}g\, d\mu \biggr)\biggr\vert \, d\mu + \int_{\Omega}\biggl\vert g \biggl(f-2\int_{\Omega}f\, d\mu \biggr)\biggr\vert \, d\mu \biggr) \\& \quad \leq \biggl(\int_{\Omega}f^{2} \, d\mu \biggr)^{\frac{1}{2}} \biggl(\int_{\Omega}g^{2} \, d\mu \biggr)^{\frac{1}{2}}. \end{aligned}

The inequality (1.4) follows.â€ƒâ–¡

## 3 An application

Let $$(a_{1},b_{1}),\ldots,(a_{n},b_{n})$$ be n items of bivariate real data, $$x=\{a_{1},\ldots,a_{n}\}$$ and $$y=\{b_{1},\ldots,b_{n}\}$$, then their covariance $$\operatorname{Cov}(x,y)$$ is defined as [11]

$$\operatorname{Cov}(x,y)=\frac{1}{n}\sum_{i=1}^{n}(a_{i}-a) (b_{i}-b),$$

where $$a=\frac{a_{1}+\cdots+a_{n}}{n}$$ and $$b=\frac{b_{1}+\cdots+b_{n}}{n}$$.

For the covariance $$\operatorname{Cov}(x,y)$$, it is well known that Pearsonâ€™s product moment inequality is

$$\bigl\vert \operatorname{Cov}(x,y)\bigr\vert \leq \operatorname{SD}(x)\cdot \operatorname{SD}(y),$$

where $$\operatorname{SD}(x)=\sqrt{\frac{1}{n}\sum_{i=1}^{n}(a_{i}-a)^{2}}$$ and $$\operatorname{SD}(y)=\sqrt{\frac{1}{n}\sum_{i=1}^{n}(b_{i}-b)^{2}}$$.

Similarly, now we define this covariance of two n-tuples $$X=( x_{1},x_{2},\ldots ,x_{n})$$ and $$Y=(y_{1},y_{2},\ldots,y_{n})$$ of the unitary space $$\mathbb{H}$$ as

$$\operatorname{Cov}(X,Y)=\frac{1}{n} \sum_{i=1}^{n} \langle x_{i}-a,y_{i}-b\rangle,$$

where $$a=\frac{x_{1}+\cdots+x_{n}}{n}$$ and $$b=\frac{y_{1}+\cdots+y_{n}}{n}$$.

Set $$\alpha_{i}=x_{i}-a$$ and $$\beta_{i}=y_{i}-b$$, $$i=1,\ldots,n$$. Note that

\begin{aligned} x_{i}\otimes_{A}y_{i}&=\langle \alpha_{i}+a,\beta_{i}+b\rangle-\langle\alpha _{i}+a,b\rangle-\langle a,\beta_{i}+b\rangle \\ &=\langle\alpha_{i},\beta_{i}\rangle-\langle a,b\rangle \\ &=\langle x_{i}-a,y_{i}-b\rangle-\langle a,b\rangle. \end{aligned}

Hence, (1.3) can be written in the following form:

$$\sum_{i=1}^{n}\bigl\vert \langle x_{i}-a,y_{i}-b\rangle-\langle a,b\rangle\bigr\vert \leq \|X\| \cdot\|Y\|,$$
(3.1)

where $$\|X\|= (\sum^{n}_{i=1}\|x_{i}\|^{2} )^{1/2}$$ and $$\|Y\|= (\sum^{n}_{i=1}\|y_{i}\|^{2} )^{1/2}$$.

Using the triangle inequality on the left side of (3.1), we obtain

$$\bigl\vert n \operatorname{Cov}(X,Y)-n\langle a,b\rangle\bigr\vert \leq\|X\| \cdot\|Y\|.$$

Finally, we can simply state the above result, as follows.

### Theorem 3

Let $$X=( x_{1},x_{2},\ldots,x_{n})$$ and $$Y=(y_{1},y_{2},\ldots,y_{n})$$ be two n-tuples of the unitary space $$\mathbb {H}$$, then

$$\bigl\vert \operatorname{Cov}(X,Y)-\langle a,b\rangle\bigr\vert \leq \frac{1}{n} \|X\|\cdot\|Y\|.$$
(3.2)

## References

1. Dragomir, SS: A survey on the Cauchy-Buniakowsky-Schwarz type discrete inequalities. J. Inequal. Pure Appl. Math. 4, Article 63 (2003)

2. Ackermann, N: A Cauchy-Schwarz type inequality for bilinear integrals on positive measures. Proc. Am. Math. Soc. 133, 2647-2656 (2005)

3. Alzer, H: A refinement of the Cauchy-Schwarz inequality. J. Math. Anal. Appl. 168, 596-604 (1992)

4. Alzer, H: On the Cauchy-Schwarz inequality. J. Math. Anal. Appl. 234, 6-14 (1999)

5. Carbery, A: A multilinear generalization of the Cauchy-Schwarz inequality. Proc. Am. Math. Soc. 132, 3141-3152 (2004)

6. Dragomir, SS: On the Cauchy-Buniakowsky-Schwarz inequality for sequences in inner product space. Math. Inequal. Appl. 3, 385-398 (2000)

7. Masjed-Jamei, M: A functional generalization of the Cauchy-Schwarz inequality and some subclasses. Appl. Math. Lett. 22, 1335-1339 (2009)

8. MitrinoviÄ‡, DS, PeÄ‡ariÄ‡, JE, Fink, AM: Classical and New Inequalities in Analysis. Kluwer Academic, Dordrecht (1993)

9. Wada, S: On some refinement of the Cauchy-Schwarz inequality. Linear Algebra Appl. 420(2-3), 433-440 (2007)

10. Rudin, W: Real and Complex Analysis. McGraw-Hill, New York (1987)

11. Fisher, RA: Statistical Methods, Experimental Design, and Scientific Inference. Oxford University Press, New York (1990)

## Acknowledgements

This work was partially supported by the National Natural Science Foundation of China (Grant No.Â 11171053).

## Author information

Authors

### Corresponding author

Correspondence to Leng Tuo.

### Competing interests

The author declares to have no competing interests.

## Rights and permissions

Reprints and permissions

Tuo, L. Generalizations of Cauchy-Schwarz inequality in unitary spaces. J Inequal Appl 2015, 201 (2015). https://doi.org/10.1186/s13660-015-0719-z